PENGEMBANGAN MESIN PENGIRIS SINGKONG DENGAN MENGGUNAKAN PIRINGAN GERGAJI SEBAGAI DUDUKAN PISAU PEMOTONG - Nursyafri Hafniza; Islami Fatwa; Abubakar Abubakar; Taufiq Taufiq; Munzir Absa (Steam Engineering, 2026)
The increasing number of large companies entering the cassava chips production industry has raised concerns among small-scale producers. This is due to the fact that large-scale manufacturers are capable of producing and marketing their products on a mass scale, while small producers still rely on manual processes, such as peeling cassava and draining it after frying. Such manual methods require a considerable amount of time and labor, which consequently limits the production capacity of small-scale businesses. Therefore, the design and innovation of an automatic cassava slicing machine can serve as an alternative production tool for small-scale cassava chip producers. The automatic cassava slicer is expected to improve the productivity level of these producers. The lengthy process of slicing cassava manually has been a major obstacle in increasing production output. The objective of this research is to design the stages of the manufacturing process of an automatic cassava slicing machine and to conduct testing of the machine using a circular saw blade as the cutter holder. The type of research applied is experimental. The results of this study on the development of the cassava slicing machine using a circular saw blade are as follows: The cassava slicing machine employs a circular saw blade as the cutting tool and is powered by an electric motor with specifications of 220V~50Hz, 125W output power, and 1.55A input current. The machine is capable of producing 600 grams of sliced cassava per minute. The total cost required for manufacturing the machine using a circular saw blade is IDR 751,000. Based on the feasibility test conducted with two media experts, it was found that the ergonomics aspect scored 84%, the technical aspect scored 86.6%, and the aesthetic aspect scored 70%. Thus, the overall feasibility percentage reached 82%, indicating that the cassava slicing machine is considered suitable for use.